PENERAPAN DESA PEDULI GAMBUT DI DESA SAWAHAN KECAMATAN CERBON KABUPATEN BARITO KUALA - Jaelani, Achmad; Ni’mah, Gusti Khairun (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2016)
Sawahan Village is one of the Transmigration villages in the Cerbon sub-district, Barito Kuala district, South Kalimantan province. This village has a vast expanse of rice fields and 90% of the people work as farmers. Sawahan village has an area of 5,950 ha with productive land of 1,200 ha which is mostly in the form of peatland. The land of the sawahan village is located near the tidal river flow containing low pH with high acidity levels ranging from 3,5 to 4,5. Land in the area is a type of peat land (black brown), so that not all plants, livestock and fish can grow / live except plants, fish, livestock that can adapt to this condition. Peatlands have their own difficulties in managing them. Some fruit plants and horticulture can live after being adapted to the condition of the land for a long period of time but given a considerable amount of lime to overcome high acidity and disease resistance. With this, many transmigrant farmers have difficulty inhandling the land because some species of plants and fish cannot develop properly. For this reason a new breakthrough is needed so that this problem can be overcome and farmers are able to plant crops, fish and livestock specific to peatlands. Some of the results of the Uniska Agriculture Faculty trial which tried several plants that were adaptive to the conditions of peatlands such as Kweni Anjir, Limau Kuit, Rambutan Antalagi and Kasturi. In addition to fruit trees, there are also horticultural plants that have been tried on these peatlands, namely long beans, purple eggplant, bitter melon, tiyung chili (very spicy mini chili). For fish there are fragrant fish (cork) and catfish. Whereas livestock with Alabio ducks are resistant to peatland conditions. In addition tofruit trees, there are also horticulture plants that have been tried on these peatlands, namely long beans, purple eggplant, bitter melon, tiyung chili. The problem in this activity is how farmers make efforts in transmigrant areas by selecting mina plants, fish and livestock that are suitable for cultivation on peatlands, how to cultivate mina-plants and livestock for peatland species to get maximum results and how to pioneer marketing efforts production so that it can really increase the income of transmigrant farmers in Sawahan Village, Barito Kuala Regency.